THE RELATIONSHIP BETWEEN PRE-SERVICE TEACHERS' ATTITUDE TOWARDS STATISTICS AND ATTITUDE TOWARDS PROBABILITY - Anas Seidu Salifu; Mohammed Emmanuel Dokurugu (Jurnal Infinity, 2022)
In this study, attitudes of pre-service teachers (PSTs) towards statistics and towards probability were examined. A sample of 184 level 300 students of the Evangelical Presbyterian (E. P.) College of Education, Bimbilla who undertook the Statistics and Probability II course for the second semester of the 2020/2021 academic year was used to conduct the study. The main objective of the study was to determine PSTs attitude towards statistics, attitude towards probability, and the differences in attitude that exist among them. The study also investigated the relationship between attitudes towards statistics and attitudes towards probability. The sample was selected through purposive and simple random techniques from level 300 students who either pursue mathematics as a major or as a minor subject. Two sets of questionnaires, one for attitudes towards statistics and the other for attitudes towards probability were administered to the selected respondents. The data was analyzed using SPSS version 24 by employing both descriptive and inferential statistics such as frequency counts, percentage, mean, standard deviation, paired sample t-test, and correlation. The results revealed that pre-service teachers have a positive attitude towards statistics than probability. Also, 93.5% and 83.2% of the Pre-service Teachers respectively consider statistics and probability very useful and necessary courses that will prepare them for the job market. Again, the Pearson correlation coefficient revealed a moderate positive association between Pre-service Teachers' attitudes towards statistics and towards probability.